2019
DOI: 10.1371/journal.pntd.0007191
|View full text |Cite
|
Sign up to set email alerts
|

The importance of extracellular vesicle purification for downstream analysis: A comparison of differential centrifugation and size exclusion chromatography for helminth pathogens

Abstract: BackgroundRobust protocols for the isolation of extracellular vesicles (EVs) from the rest of their excretory-secretory products are necessary for downstream studies and application development. The most widely used purification method of EVs for helminth pathogens is currently differential centrifugation (DC). In contrast, size exclusion chromatography (SEC) has been included in the purification pipeline for EVs from other pathogens, highlighting there is not an agreed research community ‘gold standard’ for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 83 publications
5
74
0
Order By: Relevance
“…Similar to the published finding of Xu's team, our data suggested that human SAE cells are able to secrete EVs under control and cigarette smoke exposure conditions in an in vitro model. Although the differential centrifugation technique is widely used for the EV purification, we opted for the two-step procedure, i.e., precipitation reagent solution and size exclusion chromatography (SEC), as it is associated with a higher purity of EVs than differential centrifugation alone [43]. We found that CSC exposure did not cause significant differences in the concentration and size of SAE-derived EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the published finding of Xu's team, our data suggested that human SAE cells are able to secrete EVs under control and cigarette smoke exposure conditions in an in vitro model. Although the differential centrifugation technique is widely used for the EV purification, we opted for the two-step procedure, i.e., precipitation reagent solution and size exclusion chromatography (SEC), as it is associated with a higher purity of EVs than differential centrifugation alone [43]. We found that CSC exposure did not cause significant differences in the concentration and size of SAE-derived EVs.…”
Section: Discussionmentioning
confidence: 99%
“…TDE have been proposed as biomarkers, diagnostics and therapeutics, or "theranostics" [152] (Table 2). Although the EV isolation procedure is still a matter of debate, currently, the gold standard for EV purification includes differential centrifugation [153,154]. Differentially expressed proteins and genetic materials in EV recovered from tumour patients and healthy subjects are the so far most applied approach for biomarker discovery.…”
Section: Discussionmentioning
confidence: 99%
“…As EVs are heterogeneous, different isolation techniques and variations in equipment settings would enrich certain EVs subtypes while depleting others [ 158 ]. The level of EVs purity also varies, thus giving rise to difficulties in experiment reproducibility and quality control [ 159 , 160 , 161 ].…”
Section: Isolation Methods For Ev Productionmentioning
confidence: 99%